2010
DOI: 10.1603/ec09238
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of <I>Choristoneura rosaceana</I> (Lepidoptera: Tortricidae) to Two New Reduced-Risk Insecticides

Abstract: The response of field-collected populations of the obliquebanded leafroller, Choristoneura rosaceana (Harris) (Lepidoptera: Tortricidae), to chlorantraniliprole, spinetoram, spinosad, and azinphosmethyl was assessed using a diet incorporation bioassay. Populations of obliquebanded leafroller were collected from nine orchards in Chelan, Douglas, Grant, and Okanogan counties of Washington. The neonates of the F1 or F2 generation were used in all assays. The parameters of probit regression lines were estimated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 24 publications
1
41
1
1
Order By: Relevance
“…Interpopulational variation in susceptibility to spinosad among diamondback moths, Plutella xylostella (L.), from the United States has been reported by Zhao et al (2006). SigniÞcant variation also was detected in response to spinosad in Helicoverpa armigera (Hü bner) (Wang et al 2009); the bollworm Earias vittella F. (Ahmad and Iqbal Arif 2009); obliquebanded leafroller, Choristoneura rosaceana (Harris) (Sial et al 2010); and olive fruit ßy, Bactrocera oleae (Gmelin) (Kakani et al 2010). Low level of resistance to spinosad in sweetpotato whiteßy, Bemisia tabaci (Gennadius), was detected previously (Wang et al 2010b).…”
Section: Discussionmentioning
confidence: 96%
“…Interpopulational variation in susceptibility to spinosad among diamondback moths, Plutella xylostella (L.), from the United States has been reported by Zhao et al (2006). SigniÞcant variation also was detected in response to spinosad in Helicoverpa armigera (Hü bner) (Wang et al 2009); the bollworm Earias vittella F. (Ahmad and Iqbal Arif 2009); obliquebanded leafroller, Choristoneura rosaceana (Harris) (Sial et al 2010); and olive fruit ßy, Bactrocera oleae (Gmelin) (Kakani et al 2010). Low level of resistance to spinosad in sweetpotato whiteßy, Bemisia tabaci (Gennadius), was detected previously (Wang et al 2010b).…”
Section: Discussionmentioning
confidence: 96%
“…Narrow variations in chlorantraniliprole susceptibility (based on LC 50 ) were observed in Þeld populations of P. xylostella (Þvefold) (Wang et al 2010), Choristoneura rosaceana (5.3-fold) (Sial et al 2010), Cnaphalocrocis medinalis (5.8-fold) (Zheng et al 2011), Chilo suppressalis (9.4-fold) (Huang et al 2011), Spodoptera exigua (sixfold) , and Bemisia tabaci (Þvefold) (Li et al 2012). Limited variation of chlorantraniliprole susceptibility in pest Þeld populations suggested that there is no cross-resistance to chlorantraniliprole conferred by resistance to currently used insecticides (Wang et al 2010, Li et al 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Anthranilic diamides, a new class of insecticide were expected to replace some of the conventional synthetic pyrethroid, organo-phosphate, organo-chlorine, abamectin, spinosad, indoxacarb carbamates and neonicotinoid insecticides (Cao et al, 2010;Sial et al, 2010;Wang et al, 2010). They were thought to be less toxic to non-target organisms including birds, mammals, earthworms and many other arthropods (Lahm et al, 2007;Larson et al, 2012;Bontrager, 2012) and only slightly toxic to fish (U.S. EPA, 2008) but is highly toxic to Folsomia candida and Daphnia magna, and medium to very highly toxic to several insects and crustaceans (Kraggerud et al, 2010).…”
Section: Introductionmentioning
confidence: 99%